Sopc based convolutinal Encoder and Viterbi Decoder - Prof. K.S.Bhagat, Tejasweeni G. Bhangale (International Journal of Scientific Research and Management (IJSRM), 2013)
Convolutional encoding is most important technique in Code Division Multiple Acess(CDMA).CDMA uses convolutional encoder to reduce interference. Convolutional encodeing and viterbi decoding are most widely used in most communication systems because of their excellant error control. Convolutional encoding with Viterbi decoding is a FEC technique that is particularly suited to a channel in which the transmitted signal is corrupted mainly by additive white gaussian noise (AWGN). The design has been implemented on SOPC using XILINX 12.2 software with supporting simulation tool ISim.